The Role of AI in Making Poetry Accessible to Global Audiences: Machine Translation and Poetic Diversity (Czech Journal of Multidisciplinary Innovations, 2024)
Poetry is a powerful form of artistic expression that connects people through emotions, cultural stories, and shared human experiences. However, language has always been a barrier for poets and their audiences. Poetic language is often rich in metaphor, imagery, and cultural references, making it difficult for non-native speakers to fully appreciate the work. Fortunately, Artificial Intelligence (AI) and Machine Translation (MT) are now offering new solutions to this problem. With AI’s help, poets can share their works across language barriers, allowing readers from different cultures to access the beauty and emotion of poetry. This article explores how AI and MT are making poetry accessible to a global audience, with examples of English and Uzbek poets to demonstrate the transformative potential of these technologies